Dietary zinc intake is inversely associated with the risk of hypertension in the periodontitis population - Zhang, Yvning; Zhao, Yueyue; Zhong, Yilu; Zeng, Rui; Ye, Dongmei; Guo, Dawei; Li, Wei (Frontiers in Nutrition, 2025)
BackgroundPeriodontitis is a common chronic inflammatory disease, which is closely related to the development of several chronic diseases, including hypertension. The aim of this study was to investigate the association between dietary zinc intake and the risk of hypertension in a periodontitis population.MethodsWe used a cross-sectional study design to select 10,061 participants from the National Health and Nutrition Examination Survey (NHANES) 2009–2014. The diagnosis of periodontitis was based on measurements of periodontal probing depth and clinical attachment loss. Dietary zinc intake was assessed using a 24-h dietary review survey. We used logistic regression analysis to assess the relationship between dietary zinc intake and hypertension, and stratified analysis and interaction tests to investigate the relationship between dietary zinc and hypertension in groups such as gender, ethnicity, and education.ResultsAmong United States adults with periodontitis, the risk of developing hypertension decreased by 1% for every 1 mg increase in daily dietary zinc intake (OR = 0.99, p = 0.011). Also, we found that high dietary zinc intake was associated with a lower risk of hypertension (OR = 0.84, p = 0.015).ConclusionThis study provides evidence that dietary zinc intake reduces the risk of hypertension in periodontitis patients. These findings suggest that monitoring and optimizing zinc nutritional status in periodontitis populations is important for hypertension prevention and treatment.